PENYUSUNAN RENCANA STRATEGIS SISTEM INFORMASI DAN TEKNOLOGI INFORMASI (SI/TI) ORGANISASI BISNIS UNIVERSITAS MUHAMMADIYAH KOTABUMI MENGGUNAKAN WARD PEPPARD - Sigit Gunanto; Anggi Riko Saputra (Sienna, 2020)
Improve the quality of education services with the contribution of information systems, operational utility and business support for the organizatio. Information systems and information technology are applied in various teaching and learning process activities in an educational institution not something that is complementary and additional, but rather a need to improve the process and results of the implementation of education carried out by higher education, because it is necessary to manage this information by building a Information Systems (IS) and supported by well lanned Information Technology (IT) so that it becomes an added value for institutionin increasing competitiveness. The Ward and Peppard method is a form of strategic planning for information systems in an organization/company. With this method, various factors that arise in the organization, both internal and external, are analyzed as such to obtain a new strategy. The research was conducted at Universitas Muhammadiyah Kotabumi, data collection was carried out by conducting interviews, observing and studying documents. The results of this study are a strategic plan that can be embodied in a portfolio that can be used as a reference for planning information systems at Universitas Muhammadiyah Kotabumi